Polyamine-mediated mechanisms contribute to oxidative stress tolerance in Pseudomonas syringae - Solmi, Leandro (2023)
Bacterial phytopathogens living on the surface or within plant tissues may experience oxidative stress because of the triggered plant defense responses. Although it has been suggested that polyamines can defend bacteria from this stress, the mechanism behind this action is not entirely understood. In this study, we investigated the effects of oxidative stress on the polyamine homeostasis of the plant pathogen Pseudomonas syringae and the functions of these compounds in bacterial stress tolerance. We demonstrated that bacteria respond to H2O2 by increasing the external levels of the polyamine putrescine while maintaining the inner concentrations of this compound as well as the analogue amine spermidine. In line with this, adding exogenous putrescine to media increased bacterial tolerance to H2O2. Deletion of arginine decarboxylase (speA) and ornithine decarboxylate (speC), prevented the synthesis of putrescine and augmented susceptibility to H2O2, whereas targeting spermidine synthesis alone through deletion of spermidine synthase (speE) increased the level of extracellular putrescine and enhanced H2O2 tolerance. Further research demonstrated that the increased tolerance of the ΔspeE mutant correlated with higher expression of H2O2-degrading catalases and enhanced outer cell membrane stability. Thus, this work demonstrates previously unrecognized connections between bacterial defense mechanisms against oxidative stress and the polyamine metabolism.